Kepuasan Layanan Dalam Perspektif Islam (Studi Empiris pada Usaha Cuci Mobil Tasmin Mojokerto) - M. Adi Trisna Wahyudi; Nadia Armadani (Journal of Islamic Management, 2023)
This study aims to illustrate how service satisfaction is an Islamic perspective on car wash businesses. Researchers collect data by means of interviews and documentation. The subject of this study was Mr. Tasmin's car wash business in Mojokerto The data analysis technique used was to use the concept of Miles and Huberman. The research findings produced by researchers are that customers feel comfortable if the price set is more affordable and the employee's attitude or actions to the customer seem good.